PERIODONTAL STATUS AND TREATMENT NEEDS AMONG THE PALESTINIAN REFUGEES LIVING IN THE UNITED NATIONS CAMPS IN JORDAN - Fouad Houssain M. H. Al-Bayati (Faculty of Dentistry, Universitas Indonesia, 2006)
A periodontal health survey, using the WHO criteria 1997, was conducted among 585 Palestinian refugees living in the United Nations Camps in Jordan. The sample consists of 363 females and 222 males aged 5-54 years. The purposes of this study were to determine the prevalence and the severity of periodontal disease and treatment needs among this population and to correlate the periodontal status with age and gender. By using WHO periodontal probes, the community periodontal index (CPI), the treatment needs (TN) and loss of attachment (LA) were measured for each subject. The number of permanent loss was also recorded. Females were found to have worse periodontal conditions than males. Also, a significant age difference was present. All subjects of the present population had experienced periodontal disease, where 34$ and 43% had a shallow pocket of 4-5 mm and deep pocket of 6 mm or more respectively. The results of this study have shown that 5.48 of sextant per subject in this population were with bleeding or higher, 4.8 with calculus or higher, 2.48 with shallow pockets or higher and 0.88 with deep pocket. This study demonstrated that the loss of attachment increased significantly with increasing age and 2% of this population had normal level of periodontal attachment, with the rest of them (58%) had different amounts of attachment loss. Almost all subjects of this population needed oral hygiene instructions, scaling and/or removal of overhangs and 43% of them needed complex periodontal treatment. The mean number of loss of permanent teeth was among this population with significant age and gender differences. Our data indicated that high prevalence and severity of periodontal disease were observed in this population require programs both for prevention and treatment.